Shortage of public transport services in the sural areas of Limpopo Province : causes, challenges and effects - Mabeba, S. J.; Mmila, L. M. (International Conference on Public Administration and Development Alternatives (IPADA), 2020)
In an economic, political, social and environmental context, public transport is regarded as the most important and safe transport which allow physical movement of people. Lack of sufficient public transport services (Taxis and Buses) in rural areas remains a concern in Limpopo Province. This is not only a concern for the society but the government in particular. Communities are struggling on a daily basis to access various destinations of their choice due to shortage of public transport. Amongst other places, some households find it challenging to access Central Business Districts (CBD's). Consequently, there are negative effects and consequences that could arise because of shortage of public transport services. The aim of this paper is to highlight the main causes, challenges and effects of shortage of public transport in the rural areas of Limpopo Province. The paper adopted a desktop content analysis method. This involves systematic review of literature with specific reference to journal articles, conference articles, newspapers, books and official reports. The paper successfully unpacked the causes, challenges and effects of shortage of public transport in rural areas. It must however be acknowledged that not all rural areas in Limpopo Province have adequate public transport services. As a result, rural commuters are struggling to conveniently access various destinations such as health care facilities (clinics and hospitals) shopping complex and workplaces. Insufficient public transport can compromise the safety of rural communities. Sometimes commuters have no choice but to use private transport of unknown motorists that tend not to be safe. Therefore, this makes rural commuters to be vulnerable to immoral practices such as rape, kidnapping and robbery along the way. The major finding of this article is that the absence of proper road infrastructure is still a major challenge, which makes public transport to be limited. The paper concludes by proposing measures that can be executed in an attempt to increase and improve mobility in rural areas. Keywords: Causes, Challenges, Effects, Immoral practices, Safety
Journal article published in The International Conference on Public Administration and Development Alternatives 07 - 09 October 2020, Virtual Conference
Keywords: Causes; Challenges; Effects; Immoral practices; Safety; Transportation